2002
DOI: 10.1021/bi0260785
|View full text |Cite
|
Sign up to set email alerts
|

Metal Binding to Saccharomyces cerevisiae Ferrochelatase

Abstract: Ferrochelatase is the terminal enzyme in the heme biosynthetic pathway. It catalyzes the insertion of ferrous iron into protoporphyrin IX to produce protoheme IX. The crystal structures of ferrochelatase from Saccharomyces cerevisiae in free form, in complex with Co(II), a substrate metal ion, and in complex with two inhibitors, Cd(II) and Hg(I), are presented in this work. The enzyme is a homodimer, with clear asymmetry between the monomers with regard to the porphyrin binding cleft and the mode of metal bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
69
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 35 publications
6
69
0
Order By: Relevance
“…6D); this should result in a longer trajectory between the glutamate residues and thus slower metal transfer, which might account for the increase in its K m Fe 2ϩ value. The mode of metal substrate interaction proposed here is consistent with the recent studies of metal binding in yeast ferrochelatase (13,46). In this model, metal binding requires the conserved His 209 (murine numbering) and occurs on the same side of the active site as that of porphyrin binding, whereas the distal residues, including glutamates in the -helical region, play a regulatory role by promoting metal release from the primary binding site (46).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…6D); this should result in a longer trajectory between the glutamate residues and thus slower metal transfer, which might account for the increase in its K m Fe 2ϩ value. The mode of metal substrate interaction proposed here is consistent with the recent studies of metal binding in yeast ferrochelatase (13,46). In this model, metal binding requires the conserved His 209 (murine numbering) and occurs on the same side of the active site as that of porphyrin binding, whereas the distal residues, including glutamates in the -helical region, play a regulatory role by promoting metal release from the primary binding site (46).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the crystal structures of human and yeast ferrochelatases demonstrated that the active site entrance is delimited by two, oppositely located loops, which are rich in hydrophobic residues (12,36) and were previously hypothesized to facilitate membrane association (12,36). Further, a few positively charged residues in these loops were suggested to interact with the phosphate groups of the membrane phospholipids (13). One of these loops surrounding the active site entrance corresponds to the murine ferrochelatase sequence Gln 248 -Leu 257 , and consistent with the above hypothesis, we observed an accumulation of positively charged amino acid substitutions at the C-terminal hydropho- activity was determined by a continuous fluorimetric assay using protoporphyrin and Fe 2ϩ as substrates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations